Electronic structure-sunlight driven water splitting activity correlation of (Zn1-yGay)(O1-zNz) - Rajaambal, Sivaraman; Yadav, A. K.; Jha, Shambhu Nath; Bhattacharyya, Dibyendu; Gopinath, Chinnakonda S. (Physical Chemistry Chemical Physics, 2014)
(Zn1-yGay)(O1-zNz) (y <= 0.10; z <= 0.15) solid solutions have been investigated for their electronic structure and visible light photocatalytic activity, and a correlation was found between them. (Zn1-yGay)(O1-zNz) with ZnO as the major component have been synthesized by a solution combustion method in 10 minutes using simple raw materials. The local structures of Zn K edge and Ga K edge, and changes in the chemical environment with the incorporation of Ga and N in ZnO were determined by EXAFS study. EXAFS and XRD results suggested the dissolution of GaN in the ZnO lattice. The homogeneity of the solid solution was demonstrated from HRTEM studies. Photoluminescence studies revealed the creation of a new band at the top of the ZnO valence band (VB), and thus the broadening of the VB of (Zn1-yGay)(O1-zNz) or a decrease in the band gap was attributed to the origin of visible light absorption. UV-Vis spectral studies showed light absorption up to 550 nm, which directly supports the VB broadening. Predominant oxygen vacancies and high photocorrosion observed for ZnO were fully suppressed for (Zn1-yGay)(O1-zNz) , indicating the minimization of defects, and thus more sustainability under irradiation conditions. The bare solid solution exhibited reasonable and promising activity for solar hydrogen evolution and photoelectrochemical current generation at 0 V. The present work explained factors such as the preparation method, single phase structure with the stabilization of integral parts, homogeneity in the structure, compensation of oxygen vacancies, and suppression of the density of recombination centres that play a pivotal role in realizing solar energy harvesting.